Environmental Risk Factors for Parkinson's Disease: A Critical Review and Policy Implications - Atterling Brolin, Kajsa; Schaeffer, Eva; Kuri, Ashvin; Rumrich, Isabell Katharina; Schumacher Schuh; Artur Francisco; Darweesh, Sirwan K. L.; Kaasinen, Valtteri; Tolppanen, Anna-Maija; Chahine, Lana M.; Noyce, Alastair J. (Wiley Periodicals LLC, 2025)
The age-standardized prevalence of Parkinson's disease (PD) has increased substantially over the years and is expected to increase further. This emphasizes the need to identify modifiable risk factors of PD, which could form a logical entry point for the prevention of PD. The World Health Organization (WHO) has recommended reducing exposure to specific environmental factors that have been reported to be associated with PD, in particular pesticides, trichloroethylene (TCE), and air pollution. In this review we critically evaluate the epidemiological and biological evidence on the associations of these factors with PD and review evidence on whether these putative associations are causal. We conclude that when considered in isolation, it is difficult to determine whether these associations are causal, in large part because of the decades-long lag between relevant exposures and the incidence of manifest PD. However, when considered in tandem with evidence from complementary research lines (such as animal models), it is increasingly likely that these associations reflect harmful causal effects. Fundamentally, whilst we highlight some evidence gaps that require further attention, we believe the current evidence base is sufficiently strong enough to support our call for stronger policy action.